Formulation of Yodium Leaf Extract (Jatropha Multifida L.) Cream for Cuts Healing in Wistar Male Rats (Rattus novergicus) - Tunik Saptawati; Eka Lidia Sari; Novita Dwi Dahliyanti (STIKES Telogorejo Semarang, 2023)
Yodium plant (Jatropha multifida L) has pharmacology effect as antibacterial, antioxidant, and anti-inflammatory. Yodium plant contain chemical compounds, namely alkaloids, flavonoids, phenols, and tannins which have benefits in helping the healing process of cuts. The aim of this study was to determine the difference in wound healing time in rats (Rattus norvegicus strain wistar) using Yodium leaf extract cream with concentrations of 5%, 10%, and 15%. This research is a true experiment. The cuts healing were carry out on Wistar male rats that smeared by yodium leaf extract cream and be observed its healing process. The cream preparations were tested for physical quality including organoleptic test, homogeneity, pH test, spreadability test, adhesion test, and viscosity test. The results of the organoleptic test of the three formulas have a green color, distinctive aroma, and semi-solid consistency. Test the homogeneity of the three homogeneous preparations. The pH test of the three cream preparations met the pH test requirements of 4-8. Spreadability test, the three cream preparations met the requirements of 4-7 cm. In the adhesion test, the three preparations met the requirements of 2-300 seconds. The cream was applied to the backs of 0.1-gram rats with use three times a day. Coral plant (Jatropha multifida L) has healing effectiveness againts cuts in white rats (Rattus novergicus strain wistar). The cream preparation with 15% concentration of yodium leaves extract concentration was more effective in the wound healing process for 9 days. Keywords : Yodium leaf extract (Jatropha multifida L), Cream, Cuts, healing process